Mixed Classes, Mixed Methods: Writing Students’ Attitudes about Collaborative and Intercultural Learning - D. Michael Keleher (Networks: An Online Journal for Teacher Research, 2016)
This article describes a two-semester study of mixed (native and non-native speaking) writing groups in developmental college writing classes. The teacher assigned and observed writing activities and collected survey and interview data to determine the impact on the students’ perceived writing abilities and attitudes toward paired and small group work. The findings suggest that the benefits of collaborative learning are dependent on the degree of peer accountability and the teacher’s care in designing the activities. With mixed language background English classes becoming the norm, teachers might consider the possibilities for collaborative learning as a means for providing further emersion for non-native speakers and opportunities for mentoring and intercultural learning for native speakers.